Law nº 13.344/2016 and the new techniques for the localization of human trafficking victims and suspects: effectiveness, legality and constitutional adequacy - Cleopas Isaías Santos; Samyr Béliche Vale (Revista Brasileira de Direito Processual Penal, 2017)
The Law no. 13.344/2016 brought important repercussions to the Brazilian criminal investigation, among which the most significant one was the possibility of police authorities requesting from telephone companies the necessary technical means to locate victims and/or suspects of human trafficking. This localization is made through the identification of mobile devices, like cell phones. This article aims to answer the following issue: are the available and commonly used technical means effective in the localization of human trafficking victims and suspects? For this purpose, it is assumed that the technical means typically used in this process are not effective. In light of this, it is suggested the use of the GPS tool, which technically does not qualify as a "signal" and presumes the license of data network with financial costs. Therefore, it is analyzed who must bear said costs - the State, the companies or the consumers, as well as the legality and constitutionality of the use of this technique. The subject will be approached mostly through the deductive method.